Optimalisasi Pendapatan Non-Aeronautika Bandar Udara: Strategi Bisnis Iklan dan Pengembangan Fasilitas Lounge - Raden Muhammad Ilhanur Akib; Muhammad Fachri; Nawang Kalbuana (UNIVERSITAS SERAMBI MEKKAH, 2024)
a place for taking off passengers, a place for loading and unloading goods, a place for intra and intermodal transportation, and so on. aviation safety facilities owned as well as basic facilities and other supporting facilities. The airport has parts, starting from the apron, terminal, taxiway and runway. The airport is a place for the transfer of transportation modes and the transfer of aviation service users. Airports have revenue from various sources, PJP2U, PJP4U and so on. In general, airports have a stigma and understanding that airports are only a place or location in the use of air transportation modes, so users often think that airports are places to get on and off flight service users. By optimizing the rental of advertising media and the development of Lounge Facilities at Yogyakarta International Airport, flight service users and the public have the view that airports can advertise products / businesses and make optimal use of facilities at the airport with the aim of introducing and reaching as many people as possible to know the products / businesses owned by advertising tenants later and also enjoy the facilities at the airport, especially in the Lounge. Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. This article reviews the factors that influence Non-Aeronautical Revenue Sources at YIA Airport, namely Optimization of Advertising Media Business, Development of Lounge Facilities at YIA Airport. The purpose of writing this article is to build hypotheses of influence between variables to be used in further research. The results of this literature review article are: 1) Optimization of Advertising Media Business affects Non-Aeronautical Revenue Sources at YIA Airport; 2) Development of Lounge Facilities at YIA Airport affects Non-Aeronautical Revenue Sources at YIA Airport.